2021
DOI: 10.3390/jcm10112391
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers of Colorectal Cancer (CRC)—Their Utility in Diagnosis and Prognosis

Abstract: The global burden of colorectal cancer (CRC) is expected to increase, with 2.2 million new cases and 1.1 million annual deaths by 2030. Therefore, the establishment of novel biomarkers useful in the early diagnosis of CRC is of utmost importance. A number of publications have documented the significance of the overexpression of several specific proteins, such as inflammatory mediators, in CRC progression. However, little is known about the potential utility of these proteins as circulating blood tumor biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 111 publications
(234 reference statements)
0
17
0
Order By: Relevance
“…Colorectal cancer (CRC) is the 3rd most common cancer [1,2], with approximately 1.8 million cases diagnosed in both males and females in 2020 [3] and second in terms of death rates globally [4]. Approximately 25% of CRC patients exhibites metastatic disease at the diagnostic stage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the 3rd most common cancer [1,2], with approximately 1.8 million cases diagnosed in both males and females in 2020 [3] and second in terms of death rates globally [4]. Approximately 25% of CRC patients exhibites metastatic disease at the diagnostic stage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several potential mechanisms have been hypothesized to explain the associations between elevated CRP levels and poor prognosis of CRC. First, elevated CRP levels may reflect aggressive phenotypes of CRC, such as large tumor size, advanced tumor stage, and the presence of distant and lymph node metastases, which are associated with poor prognosis 22 . Second, although CRP per se is unlikely to directly promote cancer development, the serum concentration of CRP represents the magnitude and nature of inflammation in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works showed that serum CSF-1 has great value in the diagnosis and progression of colorectal cancer (CRC), making it an independent prognostic factor for the survival of patients with CRC 72 . As mentioned before, increased CSF-1R, CSF-1 and IL-34 expression in primary CRC was associated with a mesenchymal-like subtype and tumor invasion as well as distant metastasis 24 , 72 . Recently, immunotherapy has gradually become the focus of cancer treatment.…”
Section: Expression and Significance Of Csf-1 And Csf-1r In Gastrointestinal Malignant Tumorsmentioning
confidence: 99%
“…2 ). A study investigated the effect of CSF/CSF-R on the progression of colon cancer and pancreatic cancer in a mouse model and the results showed that in the absence of CSF-R, macrophage-related tumor cytotoxicity was amplified, indicating that CSF/CSF-R is an important clinical application target for controlling tumor microenvironment and gastrointestinal tumor progression 72 , 78 .…”
Section: Expression and Significance Of Csf-1 And Csf-1r In Gastrointestinal Malignant Tumorsmentioning
confidence: 99%